2019
DOI: 10.3390/antiox8080248
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasound-Assisted Extraction of Phenolic Compounds from Black Locust (Robiniae Pseudoacaciae) Flowers and Comparison with Conventional Methods

Abstract: The aim of this study was to optimize the ultrasound-assisted extraction of phenolic compounds from black locust (Robiniae pseudoacaciae) flowers using central composite design. The ethanol concentration (33–67%), extraction temperature (33–67 °C), and extraction time (17–33 min) were analyzed as the factors that impact the total phenolic content. The liquid-to-solid ratio of 10 cm3 g−1 was the same during extractions. The optimal conditions were found to be 59 °C, 60% (v/v) ethanol, and extraction time of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…The results showed that extraction time had the greatest influence on the total polyphenolic content, followed by the extraction temperature and ethanol concentration [40]. The optimal extraction conditions were 60% (v/v) ethanol, 59 • C, and 30 min at the liquid-to-solid ratio of 10 cm 3 g −1 [40]. Moreover, the UAE gave a higher yield of polyphenols than the maceration and Soxhlet extraction [40].…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…The results showed that extraction time had the greatest influence on the total polyphenolic content, followed by the extraction temperature and ethanol concentration [40]. The optimal extraction conditions were 60% (v/v) ethanol, 59 • C, and 30 min at the liquid-to-solid ratio of 10 cm 3 g −1 [40]. Moreover, the UAE gave a higher yield of polyphenols than the maceration and Soxhlet extraction [40].…”
mentioning
confidence: 98%
“…The most common of such "green methods" are microwave assisted (MAE), ultrasound assisted (UAE), pulsed electric field assisted, and enzyme assisted extractions, infrared irradiation (IR), pressurized liquid and supercritical fluid extractions [39]. Gajic et al [40] investigated the optimal conditions for isolating polyphenols from black locust (Robiniae pseudoacaciae) flowers using UAE. The results showed that extraction time had the greatest influence on the total polyphenolic content, followed by the extraction temperature and ethanol concentration [40].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The significance of each coefficient was determined using the f -test and p-value. According to the results, the model was highly significant when the computed f -value was greater than the tabulated f -value and the probability value was low (p < 0.05) [25]. ANOVA showed that the model's f -values were 9.09 and 5.28 for the TPC and AA, respectively, with probability (p < 0.001), implying there was only a 0.1% chance that this large f -value occurred because of noise and the model was remarkably significant and can be used for subsequent optimization designs.…”
Section: Variablesmentioning
confidence: 95%